Oxidative status of the myocardium in response to different intensities of physical training - Guerreiro, L. F; Rocha, A. M; Martins, C. N; Ribeiro, J. P; Wally, C; Strieder, D. L; Carissimi, C. G; Oliveira, M. G; Pereira, A. A; Biondi, H. S; Monserrat, J. M; Gonçalves, C. An (Physiological research, 2016)
The intensity of exercise determines the metabolic pathway and the energetic substrate that is spent. Our study sought to identify the effects of different intensities of swimming on myocardial oxidative status and the blood lipid profile. Eighty Wistar rats (male and female) submitted to different intensities of a swimming regimen (low, LS; moderate, MS; or high, HS) for 16 weeks. Samples of blood and myocardium from the left ventricle were collected to determine lipid profiles and oxidative status. Reactive oxygen species (ROS) and antioxidant capacity against peroxyl radicals (ACAP), lipid profiles and lipid peroxidation was analyzed. ROS levels and ACAP were higher in male rats than in female rats overall (p<0.05). However, ACAP in the myocardium was significantly elevated in LS female rats compared to the MS and HS female rats, which had a significantly lower ACAP compared to all other groups. LS and MS training in both sexes and HS training (in females) led to significant decreases in the heart's lipid peroxidation. Amelioration of the lipid profile and reduction in oxidative damage contributed to a physiological state that benefits cardiovascular function in exercised animals. The results show that low and moderate intensity exercise promotes beneficial adaptations.
Keywords: zvířata; metabolismus lipidů; Animals; Female; Lipid Metabolism; Myocardium; Reactive Oxygen Species; kondiční příprava zvířat; myokard; Male; potkani Wistar; Physical Conditioning, Animal; Rats, Wistar; mužské pohlaví; ženské pohlaví; reaktivní formy kyslíku